Financial Literacy of the Undergraduate Students at the College of Hilly Region in Nepal: A Case of Okhaldunga Campus - थेबे Thebe टिका Tika (Okhaldhunga Journal, 2024)
This study aims to evaluate the status of financial literacy of the undergraduate students of the campus situated in a hilly region of Nepal taking into consideration of 108 students as the convenient sample respondents among from the 459 students studying at the Okaldhunga Campus, Okaldhunga. The data collected through face-to-face manner and structured Google form of questionnaire and analyzed with the help of descriptive statistics indicates that the undergraduate students did not differ by gender in respect to their level of financial knowledge. However, younger, higher-income earners, and management students demonstrated comparatively higher level of financial knowledge than their counterparts. In terms of financial behavior, respondents predominantly adopt moderate spending habits and prioritize saving for future security, commonly depositing savings into bank accounts and using additional income for fixed deposits. Most respondents track their expenses at least occasionally, with the primary motivation for saving being to create a safety net for emergencies. Regarding financial influence, many students rely on family and social media for guidance on managing their money, and parents are often the primary decision[1]makers for finances in many households.